Corporate Reputation During Economic Crisis and Its Relationship With Financial Performance: A Conceptual Model for Asean Companies - Dwi Sunu Kanto (FISIP Universitas Tanjungpura, 2016)
Corporate reputation is a growing issue for academics and practitioners. With globalization, such tactics are used especially in Western countries yet there are obvious lack of studies on corporate reputation measurement and the relationship between corporate reputation and financial performance in ASEAN companies. The literature concentrates on the US and European companies, especially on how the public rate companies, what are rating of companies, and what relationship occurs between corporate reputation and financial performance. Corporate reputation measurement during economic crisis and its relationship with financial performance in ASEAN is detailed in the model proposed.Keywords:Corporate Reputation, Financial Performance, ASEAN Companies,*This article has been presented in the international conference organized by the Faculty of Social and Political Sciences Tanjungpura University joint by ASAIHL on the Dies Natalis Untan to-50.